Does Patient Education Augment Pelvic Floor Physical Therapy Preparedness and Attendance? A Randomized Controlled Trial. Issue 2 (March 2018) - Shannon, Megan B.; Adams, W.; Fitzgerald, C.M.; Mueller, E.R.; Brubaker, L.; Brincat, C.
Abstract : Objectives: The objective of this study was to evaluate patient attendance and preparedness for pelvic floor physical therapy (PFPT) after comparing standard counseling versus standard counseling plus an educational video. Methods: A randomized controlled trial of 200 patients in a Female Pelvic Medicine and Reconstructive Surgery practice was performed in a tertiary care referral center. Participants were randomized to 1 of 2 educational modalities after being prescribed PFPT. Women either received standard handout counseling or enhanced video counseling. A sample size of 96 per group (N = 192) was needed to detect a 20% difference in PFPT attendance corresponding to a priori estimates of 50% compliance for the standard counseling group (handout) versus 70% compliance for the enhanced counseling group (handout plus video). Compliance data were assessed at least 3 months after the initial referral to determine attendance at PFPT. Results: Sixty-five percent of patients attended at least 1 PFPT visit, whereas 46.5% completed therapy. There was no difference between the standard and enhanced counseling groups in PFPT attendance ( P = 0.056) or in completion of half the recommended visits ( P = 0.17). Similarly, level of preparedness after viewing the assigned counseling modality did not differ between standard and enhanced counseling groups. For each additional completed visit, the odds of successfully completing PFPT increased by approximately 38% (odds ratio, 1.38; 95% confidence interval, 1.19–1.59). Conclusions: The addition of enhanced patient counseling did not improve patient preparedness or odds of attending PFPT. Adherence behaviors surrounding PFPT attendance are multifactorial and require further qualitative research to elucidate barriers to PFPT attendance. Abstract : Enhanced counseling with an educational video does not improve patient adherence to pelvic floor physical therapy attendance when compared with an educational handout.